BUILDING THE PHILANTROPHY SPIRIT OF YOUNG ISLAM THROUGH ISLAMIC HIGHER EDUCATION - Hasananuddin Hasananuddin; Nurman Ginting (Proceeding International Seminar of Islamic Studies, 2021)
Philanthropy has become a serious discourse along with introducing the concept of Civil Society to society, because its emergence is related to the topic of the independence of Civil Society which develops in society. It is important to realize that philanthropy is a narrative of social life that emphasizes natural human values. Philanthropy is also a concern for the younger generation to take part in carrying out various philanthropic activities. Conceptually, philanthropy is an activity that is very suitable to be instilled for the younger generation of Muslims today to be accustomed to caring for others with various voluntary social service activities in helping those in need as an expression of love between fellow human beings. The research method used in this article is descriptive qualitative research by analyzing the process..Keyword: Philanthropy, Islamic Youth, Islamic Higher Education